Phenotypic diversity of chilli Amashito from Tabasco and Chiapas, Mexico - Latournerie-Moreno, Luís; Gutiérrez-Burón, Roberto; Garruña-Hernández, René; Ruiz-Sánchez, Esaú; Lara-Martín, Alicia Ruby; Castañón-Nájera, Guillermo (Revista Mexicana de Ciencias Agrícolas, 2020)
The objective of the work was to carry out the ethnobotanical exploration, collection and in situ characterization of populations of chilli Amashito (Capsicum annuum var. Glabriusculum) from the states of Tabasco and Chiapas. The work was carried out from July to December 2017 in 24 communities in the state of Tabasco and 15 communities in the north of the state of Chiapas, Mexico. Exploration sites were chosen based on the survey of key informants (recognized collectors), market information and available literature. A survey was applied to 39 collectors, one for each study site. The sample size to collect varied between 3 and 5 plants. Twenty morphological descriptors of plant, flower and fruit from 98 populations were measured in situ. The data were analyzed by means of principal component analysis and hierarchical clusters with the 13 variables that explained the greatest morphological variation. The collectors identify nine morphotypes of chilli Amashito that are distinguished mainly by color, pigmentation, shape and size of the fruit, and these grow mainly in ecosystems of cacao, acahual, banana and milpa farms. The first three main components explain 50.2% of observed morphological variation. The populations of chilli Amashito are differentiated and grouped according to the geographical characteristics of the study sites. The populations of the northern region of Chiapas were characterized by presenting elongated and larger fruits compared to those of the Tabasco communities. It was also found that in the neighboring areas where the two study regions converge, a group of populations that shared morphological similarities was distinguished.
Keywords: in situ; characterization; morphotypes; traditional knowledge; wild populations